HUBUNGAN ANTARA SKIN PREPARATION DENGAN INFEKSI LUKA OPERASI POST SECTIO CAESAREA DI RS ACHMAD MOCHTAR BUKITTINGGI - Calvindra Leenesa; Roza Sriyanti (Universitas Andalas, 2019)
Background : Surgical wound infection is a problem that is often found today in surgery. The Indonesian Ministry of Health reported that in 2011, 55.1% of surgical wound infections were found in government hospitals. This is in line with WHO data in 2010, where the sectio caesarean rate in Indonesia was recorded at 6%. Skin preparation can be used to prevent surgical wound infection by reducing the number of germs on the skin prior to incision.Objective : To see the relationship between skin preparation and post sectio caesarea surgical wound infection at Achmad Mochtar Bukittinggi Hospital.Methods : This study was an analytical study using a cross sectional study design by looking at the subject's medical records according to the time and place of the study. Samples were all medical records of mothers giving birth by sectio caesarea in the Obstetrics and Gynecology Section of Achmad Mochtar Bukittinggi Hospital in the period 1 January 2017 to 31 December 2017. Samples were taken from populations that met the inclusion and exclusion criteria. The sample was taken using simple random sampling technique which was taken from the medical records of Achmad Mochtar Hospital Bukittinggi. Statistical analysis to assess significance used the chi-square test.Results : The sectio caesarean group that carried out skin preparation without using chlorhexidine gluconate had the highest number (59.8%), with post sectio caesarean wound infection of 70.7%.Conclusion : There was a significant relationship between skin preparation and post sectio caesarean surgical wound infection (p <0.021) at Achmad Mochtar Bukittinggi Hospital.Keywords: Sectio caesarea, skin preparation, surgical wound infection